Conclusion of the electronic administrative contract and its confirmation - Qaidar Abdalkader Saleh (الرافدین للحقوق, 2008)
The advent of the information technology revolution has resulted in the emergence of a new type of contract through modern electronic media, especially the Internet, namely electronic contracts, under which the parties to the contract the possibility of dialogue exchange through this network through the computer screen.